The TLR4‐IRE1α pathway activation contributes to palmitate‐elicited lipotoxicity in hepatocytes. Issue 7 (19th April 2018) - Shen, Chen; Ma, Wang; Ding, Lei; Li, Songtao; Dou, Xiaobing; Song, Zhenyuan
Abstract: Lipotoxicity induced by saturated fatty acids (SFAs) plays a pathological role in the development of non‐alcoholic fatty liver disease (NAFLD); however, the exact mechanism(s) remain to be clearly elucidated. Toll‐like receptor (TLR) 4 plays a fundamental role in activating the innate immune system. Intriguingly, hepatocytes express TLR4 and machinery for TLR4 signalling pathway. That liver‐specific TLR4 knockout mice are protective against diet‐induced NAFLD suggests that hepatocyte TLR4 signalling pathway plays an important role in NAFLD pathogenesis. Herein, using cultured hepatocytes, we sought to directly examine the role of TLR4 signalling pathway in palmitate‐elicited hepatotoxicity and to elucidate underlying mechanism(s). Our data reveal that palmitate exposure up‐regulates TLR4 expression at both mRNA and protein levels in hepatocytes, which are associated with NF‐κB activation. The inhibition of TLR4 signalling pathway through both pharmacological and genetic approaches abolished palmitate‐induced cell death, suggesting that TLR4 signalling pathway activation contributes to palmitate‐induced hepatotoxicity. Mechanistic investigations demonstrate that inositol‐requiring enzyme 1α (IRE1α), one of three major signal transduction pathways activated during endoplasmic reticulum (ER) stress, is the downstream target of palmitate‐elicited TLR4 activation and mechanistically implicated in TLR4 activation‐triggered cell death in response to palmitate exposure. Collectively, our data identify that the TLR4‐IRE1α pathway activation contributes to palmitate‐elicited lipotoxicity in hepatocytes. Our findings suggest that targeting TLR4‐IRE1α pathway can be a potential therapeutic choice for the treatment of NAFLD as well as other metabolic disorders, with lipotoxicity being the principal pathomechanism.